Spatiotemporal patterns of intracellular Ca2+ signalling govern hypo‐osmotic stress resilience in marine diatoms. Issue 1 (24th January 2021) - Helliwell, Katherine E.; Kleiner, Friedrich H.; Hardstaff, Hayley; Chrachri, Abdul; Gaikwad, Trupti; Salmon, Deborah; Smirnoff, Nicholas; Wheeler, Glen L.; Brownlee, Colin
Summary: Diatoms are globally important phytoplankton that dominate coastal and polar‐ice assemblages. These environments exhibit substantial changes in salinity over dynamic spatiotemporal regimes. Rapid sensory systems are vital to mitigate the harmful consequences of osmotic stress. Population‐based analyses have suggested that Ca 2+ signalling is involved in diatom osmotic sensing. However, mechanistic insight of the role of osmotic Ca 2+ signalling is limited. Here, we show that Phaeodactylum Ca 2+ elevations are essential for surviving hypo‐osmotic shock. Moreover, employing novel single‐cell imaging techniques we have characterised real‐time Ca 2+ signalling responses in single diatom cells to environmental osmotic perturbations. We observe that intracellular spatiotemporal patterns of osmotic‐induced Ca 2+ elevations encode vital information regarding the nature of the osmotic stimulus. Localised Ca 2+ signals evoked by mild or gradual hypo‐osmotic shocks are propagated globally from the apical cell tips, enabling fine‐tuned cell volume regulation across the whole cell. Finally, we demonstrate that diatoms adopt Ca 2+ ‐independent and dependent mechanisms for osmoregulation. We find that efflux of organic osmolytes occurs in a Ca 2+ ‐independent manner, but this response is insufficient to mitigate cell damage during hypo‐osmotic shock. By comparison, Ca 2+ ‐dependent signalling is necessary to prevent cell bursting via precise coordination of K + transport, and therefore is likely to underpin survival in dynamic osmotic environments.